PENGARUH KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DAN MOTIVASI MENGAJAR TERHADAP MUTU LULUSAN DI SMA/SMK SEKECAMATAN GUNUNG PELINDUNG LAMPUNG TIMUR - Heri Setiawan (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2020)
This study aims to determine: (1) The effect of the principal's managerial ability on the quality of graduates. (2) The effect of teaching motivation on the quality of graduates. (3) The effect of principals' managerial ability and teaching motivation Simultaneously on the quality of graduates in the SMA / SMK Sekecamatan Gunung Protector East Lampung. This study is a quantitative study, the population in this study were teachers in SMA / SMK Sekecamatan Gunung Pelindung in East Lampung, totaling 67 teachers. The sample in this study was 67 teachers (respondents) from 4 (four) High Schools / Vocational Schools in Gunung Pelindung District. And data processing used in this study is a questionnaire, observation and interview. The data analysis technique of this research uses simple regression and multiple regression. The results showed that: (1) There was a positive and significant influence on the managerial ability of principals on the quality of graduates with an R square value (R2) of 0.224, this shows that the managerial ability of the school principals had a good effect on the quality of graduates with a contribution of 22.4 %. There is a positive and significant influence of teaching motivation on the quality of graduates with an R square (R2) value of 0.158, this shows that the variable of teaching motivation has a pretty good effect on the quality of graduates with a contribution of 15.8%. This means that the variable managerial ability of principals and teaching motivation simultaneously obtained an R square value (R2) of 0.224, this shows that the managerial ability of school principals and teaching motivation affect the quality of graduates with a contribution of 22.4% and the remaining 77.6% was determined by other reasons outside the regression model not examined in this study. In conclusion, this shows that there is a positive and significant influence on the managerial ability of school principals and the motivation to teach together on the quality of graduates in SMA / SMK Sekecamatan Gunung Pelindung in East Lampung.